2019
DOI: 10.1177/2158244019859956
|View full text |Cite
|
Sign up to set email alerts
|

Smokers Are Extraverted in Japan: Smoking Habit and The Big Five Personality Traits

Abstract: Identifying psychological factors related to smoking habits is important to enact effective personalized treatment. We examined the relationship between the Big Five personality traits and smoking using a large and representative Japanese sample ( n = 4,563 [2,462 women]; Mage = 53.48 years, SD = 12.87, ranging from 23 to 79 years). The results of multinomial logistic regression analysis showed that current smokers were higher in Extraversion and lower in Conscientiousness than never smokers. Extraversion was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…As noted earlier, a handful of prior studies based on East Asian populations proved inconclusive (Abe et al, 2019; Iwasa et al, 2008; Shim et al, 2014; Sutin et al, 2015). Moreover, none of these studies tested biomarkers of inflammation or cardiovascular malfunction.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As noted earlier, a handful of prior studies based on East Asian populations proved inconclusive (Abe et al, 2019; Iwasa et al, 2008; Shim et al, 2014; Sutin et al, 2015). Moreover, none of these studies tested biomarkers of inflammation or cardiovascular malfunction.…”
Section: Discussionmentioning
confidence: 90%
“…However, this same association has not been observed in another study based on larger samples of Chinese, Japanese, and Taiwanese (Sutin et al, 2015). Another study showed that conscientiousness is associated with reduced smoking in Japanese (Abe et al, 2019), but this study did not test other health-relevant behaviors. One study by Iwasa et al (2008) showed that mortality rate is lower for those high in conscientiousness in a community sample of Japanese.…”
mentioning
confidence: 90%
“…Specifically, the factors of conscientiousness and neuroticism are frequently associated with risk-averse preferences [59], and extraversion is most consistently associated with risk-seeking preferences [59,60]. For example, in everyday life, extraversion is a predictor of a variety of risky behaviours, including participation in risky sports [61], involvement in traffic collisions [62], smoking [63] and financial debt [64]. Furthermore, the influence of the big five personality factors has also been explored within the context of problem gambling.…”
Section: The Role Of Personalitymentioning
confidence: 99%
“…However, the generalizability of the conscientiousness-health link is an open question because evidence for the association comes mostly from Western, individualistic societies, which are known to emphasize the importance of personal choice (Ando et al, 2007;Gelfand et al, 2011). Although evidence exists, there are relatively few studies from collectivistic societies (Yoshimura, 2000;Leung et al, 2013;Abe et al, 2019), which attach more importance to groups and societal values (Gelfand et al, 2011). The association between conscientiousness and risky health behaviors might be attenuated if the behavior itself is considered less socially deviant (Bogg and Roberts, 2004).…”
Section: Conscientiousness and Smokingmentioning
confidence: 99%